Wear-resistant member and machine using same

A Cr-based alloy material with a specific composition is used to create an abrasion-resistant member for mechanical devices, addressing the need for cost-effective materials with performance comparable to Co-based alloys.

JP7665324B2Active Publication Date: 2025-04-21HITACHI LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020206171
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-11
Publication Date
2025-04-21
Estimated Expiration
2040-12-11

AI Technical Summary

Technical Problem

There is a need for a cost-effective abrasion-resistant material for mechanical devices that can match or exceed the performance of Co-based alloy materials, which are expensive.

Method used

A Cr-based alloy material with a composition that includes Cr (40-65% by mass), Ni (15-40% by mass), Fe (10-30% by mass), Nb (5-16% by mass), Ti (0.1-0.9% by mass), W (0-2.5% by mass), C (0.6-2.5% by mass), and optional components like Cu, Si, Sn, and Al, which forms a matrix with a ferrite and austenite phase and precipitates Nb carbides for enhanced wear resistance.

Benefits of technology

The Cr-based alloy material provides wear resistance comparable to Co-based alloys while reducing material costs, and its composition ensures improved corrosion resistance and toughness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007665324000003
    Figure 0007665324000003
  • Figure 0007665324000004
    Figure 0007665324000004
  • Figure 0007665324000005
    Figure 0007665324000005
Patent Text Reader

Abstract

To provide an abrasion resistance member using a Cr base alloy material enabling a lower cost than a Co base alloy material and superior to a conventional Co base alloy material in abrasion resistance, and a machine utilizing the abrasion resistance member.SOLUTION: An abrasion resistance member includes a Cr base alloy material. The Cr base alloy material contains 40 to 65 mass% Cr, 15 to 40 mass% Ni, 10 to 30 mass% Fe, 5 to 16 mass% Nb, 0.1 to 0.9 mass% Ti, over 0 and less than 2.5 mass% W, 0.6 to 2.5 mass% C, 3 mass% or less Mo, 2 mass% or less Mn and impurities. A mass ratio Ti / Nb of the Nb and the Ti is 0.063 or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a wear-resistant material technology, and more particularly to a wear-resistant member made of a Cr (chromium)-based alloy material and a mechanical device using said wear-resistant member. [Background technology]

[0002] In mechanical devices, sliding members, rolling members, and valve members are very important members that determine the operating accuracy of the mechanical devices and strongly affect the maintenance cycles. The wear resistance of sliding members, rolling members, and valve members is one of the important characteristics that affect the lifespan of these members.

[0003] As materials with excellent wear resistance, for example, Co (cobalt)-based alloy materials such as Stellite (registered trademark) and Tribaloy (TRIBALOY is a registered trademark) have been widely used. However, Co is a relatively expensive material, and there is a strong demand for cheaper materials from the perspective of cost reduction.

[0004] As a material that is expected to reduce costs compared to Co-based alloy materials, there is an alloy material that contains Cr instead of Co. For example, Patent Document 1 (JP 2009-052084) describes an alloy material that contains, by mass%, Cr: more than 35 to 50%, Al (aluminum): 0.1 to 6%, Fe (iron): more than 0.1 to 1%, C (carbon): 0.001 to 0.015%, Si (silicon): 0.01 to 0.2%, Mn (manganese): 0.01 to 0.2%, Mg (magnesium): 0.001 to 0.03%, N (nitrogen): 0.001 to 0.01%, and further contains, if necessary, According to the above, there is disclosed a resin molding die member made of a Ni-Cr-Al-based alloy having a component composition containing one or two of the above (A) to (B) with the balance being Ni (nickel) and unavoidable impurities, in which the amount of S (sulfur) contained as the unavoidable impurities is adjusted to 0.005% or less and the amount of O (oxygen) contained as the unavoidable impurities is adjusted to 0.003% or less. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2009-052084 A Summary of the Invention [Problem to be solved by the invention]

[0006] According to Patent Document 1, the Ni-Cr-Al alloy of Patent Document 1 has almost the same hardness as conventional Ni-Cr-Al alloys, and is more corrosion resistant than conventional Ni-Cr-Al alloys. It is also said that by using a die made of the Ni-Cr-Al alloy, it is possible to reduce the wear of the die when molding resin (especially fluororesin), and to provide a die member with a long service life. It is also said that it is possible to obtain a high-toughness hardfacing material with excellent wear resistance, corrosion resistance, and powder build-up weldability.

[0007] However, in recent years, there has been an increasing demand for improved performance and efficiency of mechanical devices, and the demands placed on sliding members, rolling members, and valve members have inevitably become higher than ever before. Naturally, reducing the cost of sliding members, rolling members, and valve members is one of the most important issues.

[0008] In view of the above, an object of the present invention is to provide a wear-resistant member using a Cr-based alloy material that does not contain Co components (i.e., allows for lower costs than Co-based alloy materials) and has wear resistance equal to or greater than that of conventional Co-based alloy materials, and a mechanical device that utilizes said wear-resistant member. [Means for solving the problem]

[0009] (I) One aspect of the present invention is a wear-resistant member made of a Cr-based alloy material, The Cr-based alloy material is More than 40 mass% and not more than 65 mass% Cr; 15% by mass or more and 40% by mass or less of Ni; 10% by mass or more and 30% by mass or less of Fe; 5% by mass or more and 16% by mass or less of Nb (niobium); 0.1% by mass or more and 0.9% by mass or less of Ti (titanium); W (tungsten) exceeding 0% by mass and less than 2.5% by mass; C of 0.6% by mass or more and 2.5% by mass or less; 3% by mass or less of Mo; 2% by mass or less of Mn; and an alloy composition including impurities, The mass ratio Ti / Nb of the Nb to the Ti is 0.063 or less; The present invention provides a wear-resistant member characterized by the above-mentioned.

[0010] In the present invention, the above-mentioned wear-resistant member (I) according to the present invention can be improved or modified as follows. (i) In the alloy composition, the Ni content is higher than the Fe content, the mass ratio C / Nb of the Nb to the C is 0.11 or more and 0.16 or less, and the mass ratio Ti / Nb is 0.0062 or more. (ii) The Cr-based alloy material has a parent phase of ferrite and austenite, in which granular and / or branch-like Nb carbide phases are precipitated in an amount of 4 area % or more and 30 area % or less. (iii) The alloy composition further includes at least one of 0.1% by mass to 5% by mass of Cu (copper), 0.1% by mass to 1% by mass of Si, 0.02% by mass to 0.3% by mass of Sn (tin), and 0.005% by mass to 0.05% by mass of Al. (iv) The wear-resistant member is a sliding member, a rolling member or a valve member.

[0011] (II) Another aspect of the present invention is a mechanical device having a sliding member, a rolling member, or a valve member, The present invention provides a mechanical device, wherein the sliding member, the rolling member or the valve member is the above-mentioned wear-resistant member. Effect of the Invention

[0012] According to the present invention, it is possible to provide a wear-resistant member using a Cr-based alloy material which can be produced at a lower cost than a Co-based alloy material and has wear resistance equal to or greater than that of conventional Co-based alloy materials, and a mechanical device using the wear-resistant member. [Brief description of the drawings]

[0013] [Figure 1] 1 is a backscattered electron image by a scanning electron microscope (SEM) showing an example of a cross-sectional microstructure of a wear-resistant member of the present invention. [Figure 2A] 1 is a schematic cross-sectional view showing a power transmission device, which is an example of a mechanical device according to the present invention. [Figure 2B] FIG. 2 is a schematic cross-sectional view showing a power transmission device, which is another example of a mechanical device according to the present invention. [Figure 2C] FIG. 4 is a schematic cross-sectional view showing a valve device, which is another example of a mechanical device according to the present invention. [Figure 2D] FIG. 11 is a schematic cross-sectional view showing another valve device, which is an example of a mechanical device according to the present invention. [Diagram 3] 1A to 1C are process diagrams showing an example of a method for producing a wear-resistant member according to the present invention. [Figure 4] 1 is a SEM backscattered electron image showing an example of a cross-sectional microstructure in a test evaluation sample of Example 2. [Diagram 5] 1 is a SEM backscattered electron image showing an example of a cross-sectional microstructure in a test evaluation sample of Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present inventors have conducted extensive research and investigation into the relationship between chemical composition, metal structure, and wear resistance of Cr-based alloy materials that do not contain Co and have Cr as the main component (the component with the highest content), particularly Cr-based alloy materials that contain more than 40 mass% Cr, and have completed the present invention.

[0015] Hereinafter, the embodiments of the present invention will be described in detail with reference to the drawings. The present invention is not limited to the embodiments described herein, and can be appropriately combined with known techniques or improved based on known techniques without departing from the technical concept of the invention.

[0016] [Chemical composition of Cr-based alloy materials] As described above, the Cr-based alloy material used in the present invention is an alloy containing Cr as the maximum content component, and contains Ni, Fe, Nb, Ti, W, and C as essential components in addition to Cr, Mo and Mn as optional components, and contains impurities. In addition, the alloy may further contain one or more of Cu, Si, Sn, and Al as additional optional components. The total content of impurities is preferably 1 mass% or less. In other words, the total of the components intentionally contained is preferably 99 mass% or more.

[0017] The composition (each component) of the Cr-based alloy material used in the present invention will be described below. Note that the remaining components other than the elements described below are impurities that are difficult to control.

[0018] Cr: More than 40% by mass but not more than 65% by mass The Cr component is the maximum content component of the Cr-based alloy material of the present invention, and has the advantage of being cheaper than Co, making it possible to reduce material costs compared to conventional Co-based alloy materials. In addition, by making Cr the maximum content component, it is also possible to easily form a passive oxide film on the surface of the wear-resistant member, thereby improving corrosion resistance.

[0019] The Cr content is preferably more than 40% by mass, more preferably 45% by mass or more, and even more preferably 50% by mass or more. If the Cr content is 40% by mass or less, the cost reduction effect is weakened and the effect of improving corrosion resistance becomes insufficient. On the other hand, if the Cr content is more than 65% by mass, the melting point of the alloy becomes too high, which deteriorates the manufacturability of the wear-resistant member (increases the manufacturing cost), so the Cr content is preferably 65% ​​by mass or less.

[0020] Ni: 15% by mass or more and 40% by mass or less The Ni component is one of the main components constituting the parent phase (a mixed phase of ferrite and austenite) of the Cr-based alloy material of the present invention, and is a component that contributes to improving the ductility and toughness of the parent phase. The Ni content is preferably lower than the above-mentioned Cr content and higher than the Fe content described below. Specifically, the Ni content is preferably 15% by mass or more, more preferably 20% by mass or more, and even more preferably 25% by mass or more. If the Ni content is less than 15% by mass, the ductility and toughness of the wear-resistant member will be insufficient. On the other hand, if the Ni content exceeds 40% by mass, the wear resistance of the wear-resistant member will be insufficient, so the Ni content is preferably 40% by mass or less.

[0021] Fe: 10% by mass or more and 30% by mass or less The Fe component is also one of the main components constituting the parent phase of the Cr-based alloy material of the present invention, and is a component that contributes to ensuring toughness and hardness. The Fe content is preferably 10 mass% or more, more preferably 12 mass% or more, and even more preferably 15 mass% or more. When the Fe content becomes less than 10 mass%, If the Fe content exceeds 30% by mass, the wear resistance of the wear-resistant member becomes insufficient. On the other hand, if the Fe content exceeds 30% by mass, the σ phase (intermetallic compound phase based on the FeCr phase), which is a brittle intermetallic compound, is easily generated, and the ductility and toughness of the wear-resistant member are significantly reduced (so-called σ phase embrittlement). The Fe content is more preferably 20% by mass or less, and further preferably 17% by mass or less.

[0022] Nb: 5% by mass or more and 16% by mass or less The Nb component is an important component that combines with the C component described later to generate and precipitate a Nb carbide phase (e.g., NbC phase) and contributes to hardening and improving the wear resistance of the wear-resistant member. In addition, the Nb component dissolved in the matrix also has the effect of contributing to improving toughness. The Nb content is preferably 5 mass% or more, more preferably 6 mass% or more. If the Nb content is less than 5 mass%, the hardening and wear resistance of the wear-resistant member will be insufficient. On the other hand, the Nb content is preferably 16 mass% or less, more preferably 12 mass% or less. If the Nb content exceeds 16 mass%, the ductility and toughness of the wear-resistant member will be insufficient.

[0023] In addition, the mass ratio C / Nb of the Nb content to the C content described later is preferably 0.11 or more and 0.16 or less, more preferably 0.12 or more and 0.14 or less. If the mass ratio C / Nb is less than 0.11, the amount of Nb carbide phase generated is insufficient, and the effect of hardening and improving the wear resistance of the wear-resistant member becomes insufficient. If the mass ratio C / Nb exceeds 0.16, the excess C component forms a Cr carbide phase (for example, Cr7C3 phase, Cr 23 C6 phase) is generated and precipitated, which is a factor in reducing the corrosion resistance of wear-resistant components.

[0024] Ti: 0.1% by mass or more and 0.9% by mass or less The Ti component combines with oxygen inside the wear-resistant member to form fine Ti oxide particles, and is a component that plays a role in capturing and stabilizing excess oxygen that does not contribute to positive effects (so-called deoxidization role). In addition, the dispersed Ti oxide particles function as starting points (seeds) for the generation of Nb carbide phase, and have the effect of contributing to the fine dispersion precipitation of Nb carbide phase. Note that the present invention does not deny the possibility that a part of the Ti component may form carbides (for example, TiC or (Nb, Ti)C).

[0025] The Ti content is preferably 0.1% by mass or more, and more preferably 0.2% by mass or more. If the Ti content is less than 0.1% by mass, the amount of Ti oxide particles produced is insufficient, resulting in insufficient fine dispersion and precipitation of the Nb carbide phase (large, clumpy Nb carbide phase particles tend to precipitate), and as a result, the hardening and wear resistance of the wear-resistant member are not sufficiently improved. On the other hand, the Ti content is preferably 0.9% by mass or less, more preferably 0.7% by mass or less, and even more preferably 0.5% by mass or less. If the Ti content exceeds 0.9% by mass, the Ti oxide particles tend to become coarse and tend to be unevenly distributed on the solidified surface of the wear-resistant member together with the Nb carbide phase, which causes a decrease in the corrosion resistance and wear resistance of the wear-resistant member.

[0026] In addition, the mass ratio Ti / Nb of the Ti content to the above-mentioned Nb content is preferably 0.0062 or more and 0.063 or less, more preferably 0.01 or more and 0.05 or less. If the mass ratio Ti / Nb is less than 0.0062, the aggregated Nb carbide phase particles tend to become coarse. If the mass ratio Ti / Nb exceeds 0.063, the Ti oxide particles tend to become coarse and tend to be unevenly distributed on the solidified surface of the wear-resistant member together with the Nb carbide phase.

[0027] W: More than 0% by mass and less than 2.5% by mass The W component is an essential component (over 0 mass%) of the Cr-based alloy material of the present invention, and has the effect of improving hardness by dissolving in the matrix. The W content is preferably 0.5 mass% or more, and more preferably 1 mass% or more. On the other hand, the W content is preferably less than 2.5 mass%, more preferably 2.3 mass% or less, and even more preferably 2.1 mass% or less. If the W content is 2.5 mass% or more, a σ phase is formed, which causes a decrease in ductility and toughness.

[0028] C: 0.6% by mass or more and 2.5% by mass or less The C component is an important component that combines with the above-mentioned Nb component to generate and precipitate the Nb carbide phase, and contributes to the hardening and wear resistance improvement of the wear-resistant member. In addition, the C component also has the effect of contributing to the hardening of the wear-resistant member even if it is dissolved in the matrix. The C content is preferably 0.6 mass% or more, more preferably 0.7 mass% or more. If the C content is less than 0.6 mass%, the hardening and wear resistance improvement of the wear-resistant member becomes insufficient. On the other hand, the C content is preferably 2.5 mass% or less, more preferably 2 mass% or less, and even more preferably 1.5 mass% or less. If the C content exceeds 2.5 mass%, the Cr carbide phase is excessively generated and precipitated, which is a factor that reduces the corrosion resistance of the wear-resistant member.

[0029] As described above, the mass ratio C / Nb of the C content to the Nb content is preferably 0.11 or more and 0.16 or less, and more preferably 0.12 or more and 0.14 or less.

[0030] Mo: 3% by mass or less The Mo component is an optional component of Cr-based alloy materials, and is a component that dissolves in the matrix and contributes to improving corrosion resistance. Mo is not an essential component (its content may be 0 mass%), but in order to ensure the effect of Mo content, the Mo content is preferably 0.2 mass% or more, more preferably 0.5 mass% or more, and even more preferably 1 mass% or more. On the other hand, the Mo content is preferably 3 mass% or less, more preferably 2.5 mass% or less, and even more preferably 2 mass% or less. If the Mo content exceeds 3 mass%, it forms a σ phase, which causes a decrease in ductility and toughness.

[0031] Mn: 2% by mass or less Mn is an optional component of Cr-based alloy materials, and combines with sulfur and oxygen to form fine particles of the compound, and plays a role in capturing and stabilizing excess sulfur and oxygen that do not contribute to positive effects (so-called desulfurization and deoxidization role). By capturing and stabilizing sulfur and oxygen, Mn contributes to improving the corrosion resistance, ductility, and toughness of wear-resistant components.

[0032] Although Mn is not an essential component (the content may be 0 mass%), in order to ensure the effect of Mn inclusion, the Mn content is preferably 0.05 mass% or more. On the other hand, the Mn content is preferably 2 mass% or less, more preferably 1 mass% or less, and even more preferably 0.5 mass% or less. If the Mn content exceeds 2 mass%, coarse particles of sulfides (e.g., MnS) are formed, which causes a decrease in the corrosion resistance, ductility, and toughness of the wear-resistant member.

[0033] Impurities: Total of 1% by mass or less Representative impurities present in the Cr-based alloy material of the present invention include N, O, P, S and Ta. Next, these impurities will be briefly described.

[0034] N: 0.04% by mass or less The N component is an impurity component that reduces the mechanical properties (e.g., ductility, toughness) of the wear-resistant member when it combines with the constituents of the Cr-based alloy material to form coarse particles of a nitride phase (e.g., a Cr nitride phase). On the other hand, by controlling the N content to 0.04 mass% or less, it becomes possible to dissolve N in the matrix or form fine particles of the nitride phase, and this also has the effect of improving the mechanical properties (e.g., hardness).

[0035] O: 0.02% by mass or less The O component is an impurity component that reduces the mechanical properties (e.g., ductility, toughness) of the wear-resistant member when it combines with the constituent components of the Cr-based alloy material to form coarse particles of an oxide phase (e.g., Fe oxide). On the other hand, by controlling the O content to 0.02 mass% or less, it becomes possible to form fine particles of the oxide phase, which also has the effect of improving the mechanical properties (e.g., hardness).

[0036] P: 0.04% by mass or less The P element is an impurity element that easily segregates at the grain boundaries of Cr-based alloy materials and reduces the mechanical properties (e.g., ductility and toughness) and corrosion resistance of the grain boundaries. By controlling the P content to 0.04 mass% or less, these negative effects can be suppressed.

[0037] S: 0.005% by mass or less The S component is an impurity component that easily combines with the constituents of Cr-based alloy materials to form sulfides (e.g., Fe sulfides) with relatively low melting points, and reduces the mechanical properties and corrosion resistance of wear-resistant components. By controlling the S content to 0.005 mass% or less, these negative effects can be suppressed.

[0038] Ta: 0.2% by mass or less Ta is one of the components contained in niobium ore (e.g., pyrochlore) and is an impurity component that is easily mixed into Nb raw materials. If the Ta content is 0.2 mass% or less, there is no particular adverse effect. In other words, Ta is not a component that is intentionally contained, but it is a component that is allowed to be contained at 0.2 mass% or less.

[0039] Additional optional ingredients As described above, the Cr-based alloy material of the present invention may further contain one or more of Cu, Si, Sn, and Al as additional optional components. Next, these additional optional components will be briefly described.

[0040] Cu: 0.1% by mass or more and 5% by mass or less The Cu component is one of the optional additional components in Cr-based alloy materials, and is a component that contributes to improving corrosion resistance. When Cu is contained, its content is preferably 0.1 mass% or more and 5 mass% or less. If the Cu content is less than 0.1 mass%, the action and effect based on Cu is difficult to clarify (no particular problems occur). On the other hand, if the Cu content exceeds 5 mass%, Cu precipitates are easily generated, which is a factor in reducing the ductility and toughness of the wear-resistant member.

[0041] Si: 0.1% by mass or more and 1% by mass or less The Si component is also one of the optional additional components in Cr-based alloy materials, and plays a role in deoxidization. When Si is contained, its content is preferably 0.1 mass% or more and 1 mass% or less. If the Si content is less than 0.1 mass%, the action and effect based on Si is difficult to clarify (no particular problems occur). On the other hand, if the Si content exceeds 1 mass%, coarse particles of oxides (e.g., SiO2) are formed, which causes a decrease in the ductility and toughness of the wear-resistant member.

[0042] Sn: 0.02 mass% or more and 0.3 mass% or less The Sn component is also one of the optional additional components in Cr-based alloy materials, and plays a role in strengthening the passive film on the surface of wear-resistant members, and contributes to improving corrosion resistance (e.g., resistance to chloride ions and acidic corrosive environments). When Sn is contained, its content is preferably 0.02 mass% or more and 0.3 mass% or less. If the Sn content is less than 0.02 mass%, it is simply difficult to clarify the action and effect based on Sn (no particular problems occur). On the other hand, if the Sn content exceeds 0.3 mass%, it causes grain boundary segregation of the Sn component, which is a factor in reducing the ductility and toughness of the wear-resistant members.

[0043] Al: 0.005 mass% or more and 0.05 mass% or less The Al component is also one of the optional additional components in Cr-based alloy materials, and is a component that contributes to improving the deoxidizing effect when combined with Mn and Si. When Al is contained, its content is preferably 0.005 mass% or more and 0.05 mass% or less. If the Al content is less than 0.005 mass%, the action and effect of Al is difficult to clarify (no particular problems occur). On the other hand, if the Al content exceeds 0.05 mass%, coarse particles of oxides and nitrides (e.g., Al2O3 and AlN) are formed, which causes a decrease in the ductility and toughness of the wear-resistant member.

[0044] [Microstructure of wear-resistant components] Fig. 1 is a backscattered electron image by a scanning electron microscope (SEM) showing an example of the cross-sectional microstructure of the wear-resistant member of the present invention. As shown in Fig. 1, the wear-resistant member made of the Cr-based alloy material of the present invention has a matrix consisting of a mixed phase of ferrite and austenite, and Nb carbide phases are dispersed and precipitated in the matrix.

[0045] A detailed examination of the SEM backscattered electron image reveals that the Nb carbide phase has a granular and / or branched shape and is finely dispersed and precipitated throughout the matrix. It is believed that the wear-resistant member of the present invention exhibits excellent wear resistance due to the finely dispersed precipitation of the Nb carbide phase.

[0046] When observing the cross-sectional microstructure of the wear-resistant member, the amount of precipitation of the Nb carbide phase is preferably 4 area% or more and 30 area% or less, more preferably 5 area% or more and 20 area% or less. If the amount of precipitation of the Nb carbide phase is less than 4 area%, the effect of improving the wear resistance of the wear-resistant member cannot be sufficiently obtained. On the other hand, if the amount of precipitation of the Nb carbide phase exceeds 30 area%, the coarse-grained Nb carbide phase is likely to precipitate, and the ductility and toughness of the wear-resistant member become insufficient. The amount of precipitation of the Nb carbide phase in Figure 1 is 5.0 area% (measured by GNU Image Editing Program (GIMP, free software)).

[0047] [Wear-resistant parts and machinery] Fig. 2A is a schematic cross-sectional view showing a power transmission device, which is an example of a mechanical device according to the present invention. As shown in Fig. 2A, a gear mechanism 100 with excellent wear resistance is obtained by combining a first gear 110 and a second gear 120 (each of which is a wear-resistant member according to the present invention) made of the Cr-based alloy material of the present invention. Note that, although Fig. 2A shows a gear mechanism using spur gears, the power transmission device according to the present invention is not limited to spur gears and may use other gears (for example, internal gears, helical gears, screw gears, bevel gears, etc.).

[0048] Fig. 2B is a schematic cross-sectional view showing a power transmission device, which is another example of a mechanical device according to the present invention. As shown in Fig. 2B, a roller chain 200 with excellent wear resistance can be obtained by using a chain plate 210, a chain pin 210, and a chain roller 230 (each of which is a type of wear-resistant member according to the present invention) made of the Cr-based alloy material according to the present invention.

[0049] Fig. 2C is a schematic cross-sectional view showing a valve device, which is another example of the mechanical device according to the present invention. As shown in Fig. 2C, a fuel injection device 300 having excellent wear resistance can be obtained by using a fuel injection valve 310 and a fuel injection valve seat 320 (each of which is a type of wear-resistant member according to the present invention) made of the Cr-based alloy material according to the present invention.

[0050] Fig. 2D is a schematic cross-sectional view showing another valve device, which is an example of the mechanical device according to the present invention. As shown in Fig. 2D, by using a valve body 410 and a valve seat 420 (each of which is a type of wear-resistant member according to the present invention) made of the Cr-based alloy material according to the present invention, a valve device 400 having excellent wear resistance can be obtained. In the valve device 400, there is no particular limitation on the fluid substance to be controlled.

[0051] [Method of manufacturing wear-resistant members] Next, a method for producing the wear resistant member of the present invention will be briefly described.

[0052] Fig. 3 is a process diagram showing an example of a manufacturing method of a wear-resistant member according to the present invention. As shown in Fig. 3, first, an alloy material preparation step S1 is performed to prepare a Cr-based alloy material that is the basis of the wear-resistant member. As long as a Cr-based alloy material capable of forming a desired wear-resistant member can be obtained, there is no particular limitation on the detailed procedure of the alloy material preparation step S1. For example, the alloy material preparation step S1 may include a raw material mixing and melting step S1a in which raw materials are mixed and melted to form a molten metal so as to have a desired alloy composition, and an alloy solidification step S1b in which the molten metal is solidified / solidified to prepare a Cr-based alloy material.

[0053] In order to further reduce the content of impurities in the alloy (to refine the alloy), the raw material mixing and melting step S1a may further include a raw material alloy ingot formation step in which the molten Cr-based alloy is once solidified to form a raw material alloy ingot, followed by a remelting step in which the raw material alloy ingot is remelted to prepare a purified molten metal. There are no particular limitations on the remelting method as long as it can increase the purity of the alloy, but for example, vacuum arc remelting (VAR) can be preferably used.

[0054] The alloy solidification step S1b is not particularly limited in terms of its detailed procedure as long as it can produce a Cr-based alloy material in a form (e.g., ingot, powder) suitable for use in the next step, the forming processing step S2. For example, a casting method or an atomization method can be suitably used.

[0055] When preparing a Cr-based alloy material in the shape of a rod, wire, or tape, it is preferable to carry out an elementary process of forming an alloy ingot by casting, followed by an elementary process of plastic processing in which the alloy ingot is plastically processed to obtain a Cr-based alloy material of a desired shape. When preparing a powder of the Cr-based alloy material, an elementary process of classification may be carried out to adjust the particle size to a desired range after an elementary process of atomization (e.g., gas atomization or centrifugal atomization to obtain spherical particles). The elementary process of classification is not essential, but is preferable from the viewpoint of improving the usability of the Cr-based alloy powder.

[0056] Next, a forming process S2 is performed in which the Cr-based alloy material obtained in the alloy material preparation process S1 is used to form a formed body of a desired shape. There is no particular limitation on the forming method as long as a formed body of a desired shape can be formed. For example, when the Cr-based alloy material is an ingot, plastic processing (hot processing, cold processing, etc.) or machining (punching, cutting, etc.) can be appropriately used. Also, when the Cr-based alloy material is a powder, a powder metallurgy process can be suitably used.

[0057] Next, a surface finishing step S3 is performed to finish the surface of the Cr-based alloy formed in the forming step S2. There is no particular limitation on the surface finishing method, and conventional methods (e.g., grinding and polishing) can be used as appropriate. EXAMPLES

[0058] The present invention will be described in more detail below with reference to experimental examples, although the present invention is not limited to these experimental examples.

[0059] [Experiment 1] (Preparation of Examples 1 to 4, Comparative Example 1, and Reference Examples 1 to 2) In Examples 1 to 4 and Comparative Example 1, the alloy raw materials were mixed, and then an alloy ingot (diameter 34 mm, approximately 50 g) was produced by arc melting (in a reduced pressure Ar atmosphere) on a water-cooled copper hearth. At this time, the alloy ingot was remelted six times to homogenize the alloy ingot. In Reference Examples 1 to 2, a commercially available Co-based alloy powder was used to produce an alloy ingot (diameter 34 mm, approximately 50 g) in the same manner as in Examples 1 to 4 and Comparative Example 1. The nominal alloy compositions of Examples 1 to 4, Comparative Example 1, and Reference Examples 1 to 2 are shown in Table 1.

[0060] [Table 1]

[0061] As shown in Table 1, Examples 1 to 4 are Cr-based alloy materials that satisfy the alloy composition of the present invention, Comparative Example 1 is a Cr-based alloy material (not including W component) that is outside the alloy composition of the present invention, and Reference Examples 1 and 2 are commercially available Co-based alloy materials. Regarding impurities (N, O, P, S), they were included in the content (bal.) of the main components after confirming that the total amount was 0.1 mass% or less.

[0062] Plates (15 mm×20 mm×2 mm) were cut out from the alloy ingot prepared above, and the surfaces were polished to prepare test evaluation samples of Examples 1-4, Comparative Example 1, and Reference Examples 1-2.

[0063] [Experiment 2] (Property Investigation of Examples 1 to 4, Comparative Example 1, and Reference Examples 1 and 2) For the test evaluation samples of Examples 1 to 4, Comparative Example 1, and Reference Examples 1 and 2 produced in Experiment 1, microstructure observation and Vickers hardness evaluation were performed.

[0064] (1) Microstructural Observation The microstructure observation was performed using a scanning electron microscope-energy dispersive X-ray analyzer SEM-EDX (S-4300SE, manufactured by Hitachi High-Technologies Corporation). Fig. 4 is an SEM backscattered electron image showing an example of the cross-sectional microstructure of the test evaluation sample of Example 2, and Fig. 5 is an SEM backscattered electron image showing an example of the cross-sectional microstructure of the test evaluation sample of Example 3. Note that Fig. 1 described above is for the test evaluation sample of Example 1.

[0065] In the test evaluation samples of Examples 2 and 3 shown in Figures 4 and 5, the matrix is ​​composed of a mixed phase of a ferrite phase (α phase) and an austenite phase (γ phase) as in Figure 1, and Nb carbide phase is dispersed and precipitated in the matrix. The Nb carbide phase has a granular or branch-like shape. The amount of precipitation of the Nb carbide phase is 7.4 area % in Example 2 and 5.1 area % in Example 3 (measured by GNU Image Editing Program (GIMP, free software)).

[0066] In the Co-based alloy materials of the test evaluation samples of Reference Examples 1 and 2, although illustration is omitted, it was confirmed that since they did not contain an Nb component, an Nb carbide phase did not form or precipitate, and instead a Cr carbide phase precipitated.

[0067] (2) Vickers hardness evaluation The hardness of the alloy samples was tested and evaluated as an index of wear resistance. A Vickers hardness test (based on JIS Z 2244 (2009)) was performed on the test and evaluation samples to measure the Vickers hardness (HV). Seven points were measured (load: 1 kgf, holding time: 10 seconds) using a micro Vickers hardness tester (Matsuzawa Corporation, AMT-X7FS), and the average value of the remaining five points excluding the maximum and minimum values ​​of the seven Vickers hardness values ​​was determined as the Vickers hardness of the sample.

[0068] Regarding the Vickers hardness, the case of "440≦HV" was judged as "passed," and the case of "HV<440" was judged as "failed." The results are summarized in Table 2.

[0069] [Table 2]

[0070] As shown in Table 2, Examples 1 to 4 and Reference Examples 1 and 2 according to the present invention are judged to be "passed". On the other hand, Comparative Example 1, which does not comply with the provisions of the present invention, is judged to be "failed". From these results, it can be said that the Cr-based alloy material of the present invention has wear resistance equivalent to that of conventional Co-based alloy materials, and can be made at a lower cost than the Co-based alloy materials.

[0071] The above-mentioned embodiments and experimental examples have been described to aid in understanding the present invention, and the present invention is not limited to the specific configurations described. For example, it is possible to replace a part of the configuration of the embodiments with a configuration according to the technical common sense of a person skilled in the art, and it is also possible to add a configuration according to the technical common sense of a person skilled in the art to the configuration of the embodiments. In other words, it is possible to delete, replace, or add a part of the configuration of the embodiments and experimental examples in this specification without departing from the technical idea of ​​the invention. [Explanation of symbols]

[0072] 100... gear mechanism, 110... first gear, 120... second gear, 200…Roller chain, 210...chain plate, 220...chain pin, 230...chain roller, 300... fuel injection device, 310... fuel injection valve, 320... fuel injection valve seat body, 400... valve device, 410... valve body, 420... valve seat.

Claims

1. A wear-resistant member made of a Cr-based alloy material, The Cr-based alloy material is More than 40 mass% and not more than 65 mass% Cr; 15% by mass or more and 40% by mass or less of Ni; 10% by mass or more and 30% by mass or less of Fe; 5% by mass or more and 16% by mass or less of Nb; 0.1% by mass or more and 0.9% by mass or less of Ti; W of 1% by mass or more and less than 2.5% by mass; C of 0.6% by mass or more and 2.5% by mass or less; 3% by mass or less of Mo; 2% by mass or less of Mn; 5% by mass or less of Cu; and an alloy composition containing 1 mass % or less of impurities, The alloy composition has a higher Ni content than the Fe content, The mass ratio C / Nb of the Nb to the C is 0.11 or more and 0.16 or less, The mass ratio Ti / Nb of the Nb to the Ti is 0.0062 or more and 0.063 or less; A wear-resistant member characterized by:

2. The wear-resistant member according to claim 1, The Cr-based alloy material is a wear-resistant member having a parent phase of ferrite and austenite, in which a granular and / or branch-like Nb carbide phase is precipitated in an amount of 4 area % or more and 30 area % or less.

3. The wear-resistant member according to claim 1 or 2, A wear-resistant member which is a sliding member, a rolling member or a valve member.

4. A mechanical device having a sliding member, a rolling member, or a valve member, A mechanical device, wherein the sliding member, the rolling member, or the valve member is the wear-resistant member according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • JP1975087916A

  • High chromium alloy with excellent corrosion resistance against mixture of nitric and hydrofluoric acids

    JP1978079711A

  • Component of die for molding resin

    JP2009052084A

  • Cr-Fe-Ni-BASED ALLOY PRODUCT AND METHOD FOR MANUFACTURING SAME

    WO2018186298A1

  • Cr-Ni BASED ALLOY, RAPIDLY SOLIDIFIED MOLDED BODY MADE OF Cr-Ni BASED ALLOY, ALLOY POWDER, POWDER METALLURGY MOLDED BODY, CAST MOLDED BODY, PRODUCTION METHOD FOR Cr-Ni BASED ALLOY AND MECHANICAL EQUIPMENT USING Cr-Ni BASED ALLOY, AND PIPING MEMBER

    WO2019189531A1